2016
DOI: 10.1002/adma.201600798
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Nanocrystalline‐TiO2(B)/Carbon Nanotube Hyperdispersion Prepared via Combined Ultracentrifugation and Hydrothermal Treatments for Hybrid Supercapacitors

Abstract: Anisotropically grown (b-axis short) single-nano TiO2 (B), uniformly hyper-dispersed on the surface of multiwalled carbon nanotubes (MWCNT), was successfully synthesized via an in situ ultracentrifugation (UC) process coupled with a follow-up hydrothermal treatment. The uc-TiO2 (B)/MWCNT composite materials enable ultrafast Li(+) intercalation especially along the b-axis, resulting in a capacity of 235 mA h g(-1) per TiO2 (B) even at 300C (1C = 335 mA g(-1) ).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…There is a pair of obvious single peak at the potential of 1.73 V and 1.97 V (versus Li + /Li), corresponding to the typical Li + insertion/extraction potentials for the anatase phase TiO 2 [32,33] . Besides, there is a pair of weak peaks around 1.5 V and 1.7 V (versus Li + /Li), corresponding to the typical Li + insertion/extraction potentials for the TiO 2 (B) [27,34] . So, it can be confirmed that the hydrothermal product is mainly composed of anatase TiO 2 , while mixed with a small amount of TiO 2 (B).…”
Section: Resultsmentioning
confidence: 99%
“…There is a pair of obvious single peak at the potential of 1.73 V and 1.97 V (versus Li + /Li), corresponding to the typical Li + insertion/extraction potentials for the anatase phase TiO 2 [32,33] . Besides, there is a pair of weak peaks around 1.5 V and 1.7 V (versus Li + /Li), corresponding to the typical Li + insertion/extraction potentials for the TiO 2 (B) [27,34] . So, it can be confirmed that the hydrothermal product is mainly composed of anatase TiO 2 , while mixed with a small amount of TiO 2 (B).…”
Section: Resultsmentioning
confidence: 99%
“…Beyond that, the mesoporous nanostructured TiO 2 ‐B exhibited more favorable Li + intercalation behavior than that of pure TiO 2 ‐B nanomaterials, including the Li + diffusion kinetics, pseudocapacitive effects and so on. Various pore‐creating approaches have been developed for porous TiO 2 ‐B . Thereinto, introducing the organic precursor with instability component for the hydrothermal process was the typical approach.…”
Section: Ti‐based Oxides As Anode Materials For Libsmentioning
confidence: 99%
“…However, most of these pseudocapacitive materials operate in aqueous electrolytes, thus limiting their practical interest for high-energy supercapacitor applications. V 2 O 5 [10], H 2 Ti 3 O 7 [11,12] and TiO 2 (B) [13,14] were among the first materials showing pseudocapacitive behavior in Li + containing nonaqueous electrolytes. Although high capacity (200 mAh g −1 ) was obtained, cyclability and power performance are still a concern [15].…”
Section: Introductionmentioning
confidence: 99%